EFFECT OF ANTIOXIDANTS ON BODY WEIGHT AND BLOOD PLASMA OF BROILERS IN ENROFLOXACIN INDUCED OXIDATIVE STRESS - A. Elamaran; P. Hariharan; S. Ramesh; S. Vairamuthu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The experiment was designed to evaluate the effect of antioxidants on body weight and blood plasma in enrofloxacin induced oxidative stress. Total fifty broiler chickens divided into five groups at the age of day 38 were used for this study. Group I was treated as control, group II was treated with enrofloxacin alone, group III was treated with enrofloxacin and alpha-lipoic acid, group IV was treated with enrofloxacin and vitamin E, group V was treated with enrofloxacin and co-treatment of alpha-lipoic acid vitamin E. The results of this study suggest that enrofloxacin induced oxidative stress in broilers at the therapeutic doses can be effectively ameliorated by treating with vitamin E and alpha-lipoic acid combination than treating with either of these drugs alone.